The genome sequence of a cave spider, Troglohyphantes excavatus Fage, 1919 [version 1; peer review: 2 approved] - Tin Rožman; Martina Pavlek (Wellcome Open Research)
We present a genome assembly from a female Troglohyphantes excavatus (cave spider; Arthropoda; Arachnida; Araneae; Linyphiidae). The genome sequence has a total length of 1,028.29 megabases. Most of the assembly (94.43%) is scaffolded into 13 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 14.82 kilobases.